Unmanipulated haploidentical in comparison with matched unrelated donor stem cell transplantation in patients 60 years and older with acute myeloid leukemia: a comparative study on behalf of the ALWP of the EBMT - Nicole Santoro (Journal of Hematology & Oncology, 2018)
Abstract Background Acute myeloid leukemia (AML) is both more common and with more biologically aggressive phenotype in the elderly. Allogenic stem cell transplantation (allo-SCT) is the best treatment option in fit patients. Either HLA-matched unrelated donor (MUD) or haploidentical (Haplo) donor are possible alternative for patients in need. Methods We retrospectively compared non-T-cell-depleted Haplo (n = 250) to 10/10 MUD (n = 2589) in AML patients ≥ 60 years. Results Median follow-up was 23 months. Disease status at transplant differs significantly between the two groups (p < 10−4). Reduced intensity conditioning (RIC) was administrated to 73 and 77% of Haplo and MUD, respectively (p = 0.23). Stem cell source was the bone marrow (BM) in 52% of the Haplo and 6% of MUD (p < 10−4). Anti-thymocyte globulin (ATG) was most frequently used in MUD (p < 10−4) while post-Tx cyclophosphamide (PT-Cy) was given in 62% of Haplo. Engraftment was achieved in 90% of the Haplo vs 97% of MUD (p < 10−4). In multivariate analysis, no significant difference was found between Haplo and MUD for acute (a)graft versus host disease (GVHD) grade II–IV, relapse incidence (RI), non-relapse mortality (NRM), leukemia free survival (LFS), graft-versus-host-free-relapse free survival (GRFS), and overall survival (OS). Extensive chronic (c)GVHD was significantly higher for MUD as compared to Haplo (HR 2, p = 0.01, 95% CI 1.17–3.47). A propensity score analysis confirmed the higher risk of extensive cGVHD for MUD without differences for other outcomes. Conclusions Allo-SCT from both Haplo and MUD are valid option for AML patients ≥ 60 years of age with similar results. Transplantation from MUD was associated with higher extensive cGVHD. Our findings suggest that Haplo is a suitable and attractive graft source for patients≥ 60 with AML in need of allo-SCT.